Father’s role in infancy: examining the influence of paternal depression in the postnatal period on early father-infant interactions - Sethna, V (2009)
Background: Parental depression in the post-natal period is associated with an increased risk of adverse child outcomes. Research has consistently revealed impaired interactions of postnatally depressed mothers, and this is one pathway by which children are affected. Evidence suggests that depression can also affect fathers in the postnatal period and this influences children's development; yet we are only beginning to understand the factors that explain this intergenerational transmission. This thesis aims to examine: (i) the influence of paternal depression on father-infant interactions at three months and (ii) the potential mediating role of these early interactions in the development of later child externalizing problems. Method: In a longitudinal investigation, 118 fathers were assessed for depressive symptoms postnatally using a structured clinical interview. Observational behaviours of fathers and their infants were coded using the Global Rating Scale (GRS). Two exploratory studies were conducted on a sub-sample of depressed and non-depressed fathers, matched on age and education (n=38). In the first study, behaviours representing the paternal repertoire were measured and in the second, paternal speech was analysed. New scales were developed for both these studies. Child Externalizing behaviours at one year were measured using maternal ratings on the Child Behaviour Checklist (CBCL/1½-5). Results:Depressed fathers were more withdrawn in their interactions with their infants and more negative in their speech compared to controls. They engaged in less gentle touch, fewer episodes of excitatory arousal and less active engagement. Decreased engagement mediated the association between paternal depression and child behaviour problems. ConclusionThis study has identified aspects of father-infant interaction that are impaired by depression. These parenting behaviours may be a potential target of intervention in postnatally depressed fathers.